Econometric analysis of unemployment dynamics - Chhin, Chhorwortey (2024)
This thesis aims to explore the variables contributing towards technological growth and run it against unemployment in the Europe countries between 2010 and 2020. By using the panel data and Cross-sectional studies, we will be able to understand how certain investment or improvements in the government policies will help to not only boost the technological advancement but also reduce unemployment rate. By adopting a Fixed Effects (FE), which show significant for testing the panel data, as proven by running the against Hausman Test, we can conclude that the relationship between unemployment and the variables contributing to technology and growth unemployment is mostly negative across all the 27 Europe countries between 2010- 2020. Additionally, we uncover that some of the predictors is significant in the toward the dependent variables. The F-statistics of the model especially on the FE are significant which indicate that at least of the variables has a significant effect on the dependent variable.